(untitled) (Practitioner Research, 2020)
This study aims to examine the characteristics that are possessed by resilient people, guided by two main research questions that were asked to understand further about the situation which are (i) characteristics of resilience, and (ii) factors that contribute toresilience. Data was collected through face-to-face interview and written response. A total of three people were involved as participants by using convenient sampling. Interview transcripts and written responses were coded, analysed, and the emerging key themes were discussed. The analysis suggested that resilient people possessed characteristics such as having a positive outlook, endurance, determination, resourcefulness, and spiritual belief in overcoming problems or obstacles in life. Having these characteristicsallows individuals to persevere and contribute to their resilience. In addition, the results found that factors that contributed towards resilience are early experience, better life, goals, mindfulness and social support. This study provides an insight on how resilient people act and carry themselves to overcome adversities. It is hoped that the qualitative outcome of this study will help people, especially educators and parents to gradually build these characteristics in young people to help them to become a resilience person, despite all the struggles in life.